Evaluation of Achievements of National Educational Standards Policy at Primary Schools in Parigi Moutong District - Rizal, Rizal; Djuraid, Djuraid; Daswati, Daswati (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
This research focuses on investigations regarding the non-attainment of National Education Standards in Parigi Moutong Regency Elementary Schools. Qualitative methods are used to describe holistic education policy evaluations. In this research, the validity of the data was strengthened through various techniques such as extended participation, careful observation, triangulation, peer checking, and case analysis. The equipment used by researchers includes interview guidelines, observation guidelines, and document recording. The CIPP (Context, Input, Process, Product) evaluation model is the main basis for evaluating education policies. This model is comprehensive and can be applied to policy aspects, from curriculum to institutional policy. The evaluation results show that the achievement of National Education Standards at Parigi Moutong Regency Elementary School is still not optimal. Factors such as community participation, limited facilities, low teacher innovation, and school principal management that is not yet optimal are the main obstacles. Learning processes that are less innovative and weak management of school principals are also a concern. Educational products, such as low AKM results and the lack of development of information technology and an independent learning curriculum, are important highlights in assessing the quality of graduates and human resources for teaching staff.